Entropy Engineered Cubic n‐Type AgBiSe2 Alloy with High Thermoelectric Performance in Fully Extended Operating Temperature Range. Issue 5 (21st December 2020) - Zhu, Huaxing; Zhao, Ting; Zhang, Bin; An, Zibing; Mao, Shengcheng; Wang, Guoyu; Han, Xiaodong; Lu, Xu; Zhang, Jiangwei; Zhou, Xiaoyuan
Abstract: Developing high performance n‐type thermoelectric (TE) materials is fundamentally important for developing high efficiency TE devices. AgBiSe2, which reveals superior n‐type TE performance in a cubic phase, crystallizes in a hexagonal phase at room temperature, and typically, undergoes phase transitions to a cubic phase at a temperature above 580 K. Here, for the first time, through entropy optimization with lead‐selenides (≥9.9 mol%), the high‐temperature cubic phase of AgBiSe2 is stabilized from 300 to 800 K. Furthermore, the AgBiSe2 ‐PbSe pseudo‐binary diagram is established. The resultant alloys with optimized entropy possess unique local distorted cubic lattices, which contribute low lattice thermal conductivity approaching 0.3 W m −1 K −1 in extended operating temperature range. Consequently, a peak figure of merit zT value of ≈0.8 at 800 K and a record‐high average zT value of 0.42 for n‐type I‐V‐VI2 compounds are attained in pure phase cubic n‐type (AgBiSe2 )1− x (PbSe) x solid solutions. These results pave the way for developing new TE materials via entropy engineering. Abstract : By utilizing entropy as indicator to elucidate the interconnection between thermoelectric performance, phase transition, and the local structure, the optimum entropy increment is determined for cubic AgBiSe2 .